2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28877
|View full text |Cite
|
Sign up to set email alerts
|

Successes and Lessons Learned in an Undergraduate Computational Lab Sequence for Materials Science and Engineering

Abstract: In 2012, with a switch from quarters to semesters of instruction during the academic calendar year, the Materials Science & Engineering Department at The Ohio State University added a series of computational labs to the required undergraduate curriculum. Over the course of the next 4 academic years, the achievement of student outcomes and student feedback on the courses were monitored while minor changes were made to the curriculum. While student outcomes were generally achieved, student dissatisfaction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For instance, CMSE topics are distributed amongst the disciplinary classes at Boise State University [5] and the University of Illinois at Urbana-Champaign [6]. In contrast, Ohio State University teaches a three-semester CMSE lab course within the required curriculum [7]. Within MSE, faculty value CMSE and are increasingly incorporating these topics into the undergraduate curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CMSE topics are distributed amongst the disciplinary classes at Boise State University [5] and the University of Illinois at Urbana-Champaign [6]. In contrast, Ohio State University teaches a three-semester CMSE lab course within the required curriculum [7]. Within MSE, faculty value CMSE and are increasingly incorporating these topics into the undergraduate curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, students have mixed perceptions of CMSE. For instance, one institution with a standalone CMSE course sequence found that students responded positively to survey questions regarding the importance of computational tools [7]. Nonetheless, 24% of those students ranked the CMSE course as the least valuable course in the curriculum!…”
Section: Introductionmentioning
confidence: 99%
“…Numerous college-level engineering courses introduce MATLAB ® [1][2] [3][4] [5]. For other programming languages, research shows that small auto-graded coding exercises improve student learning in introductory programming courses [6] Though researchers have found MATLAB to be pedagogically valuable [14] [15], best practices for incorporating small auto-graded exercises into a course are still being investigated.…”
Section: Introductionmentioning
confidence: 99%